Binding of the Magnaporthe oryzae Chitinase MoChia1 by a Rice Tetratricopeptide Repeat Protein Allows Free Chitin to Trigger Immune Responses. Issue 1 (9th January 2019) - Yang, Chao; Yu, Yongqi; Huang, Junkai; Meng, Fanwei; Pang, Jinhuan; Zhao, Qiqi; Islam, Md. Azizul; Xu, Ning; Tian, Yun; Liu, Jun
Abstract : Magnaporthe oryzae –secreted chitinase suppresses chitin triggered immune response; however, rice plants mount immune response by deploying a tetratricopeptide-repeat protein or by direct recognition of this chitinase. Abstract: To defend against pathogens, plants have developed complex immune systems, including plasma membrane receptors that recognize pathogen-associated molecular patterns, such as chitin from fungal cell walls, and mount a defense response. Here, we identify a chitinase, MoChia1 ( Magnaporthe oryzae chitinase 1), secreted by M. oryzae, a fungal pathogen of rice ( Oryza sativa ). MoChia1 can trigger plant defense responses, and expression of MoChia1 under an inducible promoter in rice enhances its resistance to M. oryzae . MoChia1 is a functional chitinase required for M. oryzae growth and development; knocking out MoChia1 significantly reduced the virulence of the fungus, and we found that MoChia1 binds chitin to suppress the chitin-triggered plant immune response. However, the rice tetratricopeptide repeat protein OsTPR1 interacts with MoChia1 in the rice apoplast. OsTPR1 competitively binds MoChia1, thereby allowing the accumulation of free chitin and re-establishing the immune response. Overexpressing OsTPR1 in rice plants resulted in elevated levels of reactive oxygen species during M. oryzae infection. Our data demonstrate that rice plants not only recognize MoChia1, but also use OsTPR to counteract the function of this fungal chitinase and regain immunity.